The Conditions for the Term maqbul for Ibn Hajar in his Work Taqrib al-Tahzib - Helimy Aris; Nazri Muslim (Human Resource Management Academic Research Society, 2024)
This study concerns with the condition mentioned by Ibn Hajar for one of the terms that he decided to use in his academic work entitled Taqrib al-Tahzib. This is carried out to see the extent of Ibn Hajar’s firm decision to follow the conditions when evaluating the hadith narrators of al-kutub al-sittah. To realise this, the writer has adopted the qualitative methodology which is by delving into every angle required, related to all narrators characterised by Ibn Hajar as maqbul in his three last tabaqahs namely tabaqah no. 10, tabaqah no. 11 and tabaqah no. 12 together with all their narrations contained in al-kutub al-sittah and the printed mulhaqat al-kutub al-sittah only.